KEPUASAN PELANGGAN ROOSTER ATAS KINERJA PELAYANAN ROOSTER PADA PERGURUAN TINGGI RAHARJA - Abas Sunarya; Untung Rahardja; Ayu Wanda (Universitas Raharja, 2015)
Information service system currently has penetrated into the various elements one of which is college. Information service system has grown significantly with the increasing needs of customers for information. Of these needs we are required to always move forward and follow the development of information technology. However, the information service system ROOSTER there are some shortcomings that must be corrected to be the subject of research. Among the problems that there is a level of satisfaction of service performance Rooster. ROOSTER (